Simultaneous defect of visual fields and loss of libido--a coincidence? - Jenni, S; Seiler, R; Christ, E R; Stettler, C (Praxis (Bern. 1994), 2006)
We present the case of a 60 year old male patient with incidentally detected visual abnormalities. Detailed personal history revealed a hypogonadism that had been present for several years. Further investigations established the diagnosis of an infiltrative macroadenoma. Medical treatment with cabergoline led to a rapid regression of ophthalmologic symptoms and, subsequently, of tumor size. In male subjects symptoms of hypogonadism are often reported only late in the course of the disease, thereby leading to a generally larger tumor size at the point of diagnosis. In contrast to other pituitary tumors that are mainly treated by surgery, medical treatment with dopamine agonists is the principal therapeutic option in prolactinomas.